Human gut-derived commensal suppresses generation of T-cell response to gliadin in humanized mice by modulating gut microbiota. (April 2021) - Bodkhe, Rahul; Marietta, Eric V.; Balakrishnan, Baskar; Luckey, David H.; Horwath, Irina E.; Shouche, Yogesh S.; Taneja, Veena; Murray, Joseph A.
Abstract: The human intestinal tract is colonized by a large number of diverse microorganisms that play various important physiologic functions. In inflammatory gut diseases including celiac disease (CeD), a dysbiotic state of microbiome has been observed. Interestingly, this perturbed microbiome is normalized towards eubiosis in patients showing recovery after treatment. The treatment has been observed to increase the abundance of beneficial microbes in comparison to non-treated patients. In this study, we investigated the effect of Prevotella histicola or Prevotella melaninogenica, isolated from the duodenum of a treated CeD patient, on the induction and maintenance of oral tolerance to gliadin, a CeD associated subgroup of gluten proteins, in NOD.DQ8.ABo transgenic mice. Conventionally raised mice on a gluten free diet were orally gavaged with bacteria before and after injection with pepsin trypsin digested gliadin (PTD-gliadin). P. histicola suppressed the cellular response to gliadin, whereas P. melaninogenica failed to suppress an immune response against gliadin. Interestingly, tolerance to gliadin in NOD.DQ8.ABo mice may be associated with gut microbiota as mice gavaged with P melaninogenica harbored a different microbial diversity as compared to P. histicola treated mice. This study provides experimental evidence that gut microbes like P. histicola from treated patients can suppress the immune response against gliadin epitopes. Highlights: Patients who respond to the treatment might harbor bacteria with immunomodulatory properties. P. histicola suppressed the gliadin specific cellular response in NOD.DQ8.ABo transgenic mice. The beneficial property of P. histicola in NOD.DQ8.ABo transgenic mice may be associated with gut-microbiota modulations. P. histicola monotherapy may be a candidate for further evaluation and its possible application for CeD treatment.